GAMBARAN PERSEPSI DAN PERILAKU IBU TERKAIT PENCEGAHAN DIARE PADA BALITA DI RUANG ANAK RSUD KEFAMENANU - Yuliana Goreti Tefa; Yasinta Betan; Balbina Antonelda M Wawo (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2021)
Background: Behavior is a response to stimuli or stimuli in the tangible form that can be observed directly through activities that are a form of real action or someone’s actions. The factor’s that influence mother’s behavior in preventing diarrhea in toddles are vulnerability perception, perception of seriousness, perception of benefits and obstacles, cues or instructions from others and maternal behavior in preventing diarrhea in infants. The purpose of this study was to find out how the description of perceptions and prevention behavior associated with diarrhea in infants in the children’s room kefamenanu Regional General Hospital. Method: the type of research is quantitative with survey research design. The sample of the study was 92 mothers whose toddlers suffered from diarrhea with a purposive sampling technique. The results of the research point:the respondents had a vulnerability perception as much as 96,7 % (89 peoples), seriousness perception as much as 75,0% (69 peoples), Perception of benefits as much as 94,6% (87 peoples), perception of obstacles as much as 100% (92 peoples), instructions perception as much as 72,8% (67 peoples), Mothers behavior category as much as 72,8% (67 peoples). Conclusion:89 (96,7%) respondentshad the perception that children under five were susceptible to diarrhea. 69 (75,0%) respondentshad the perception that the diarrhea that happened to the children were serious effect. 87 (94,6%) respondents have the perception that good prevention behavior from mothers has benefits in preventing diarrhea in infants.All respondents had a good perception of maternal behavior related to diarrhea prevention in infant..as many as 67 (72,8%) respondents have a good relationship with family members related to the prevention of diarrhea in infants. As many as 89 (96,7%) respondentshave a good behavior to prevention of diarrhea in infants. Keywords: Diarrhea, Perception Picture, Mother Behavior